Copernicus for monitoring European forests: strengths, challenges and potential - Lorenzo Cesaretti; Saverio Francini; Davide Travaglini; Piermaria Corona (European Journal of Remote Sensing)
Copernicus is the European Union’s Earth Observation program, offering forest-related maps through its High-Resolution Layers (HRL). Corine Land Cover (CLC) and the Japan Aerospace Exploration Agency (JAXA) also provide map-based products on European forests. However, these maps are difficult to use due to the lack of aggregated statistics, and their consistency with official forest statistics from national forest inventories compiled by the Food and Agriculture Organisation (FAO) remains unclear. This study explores the potential of Copernicus ready-to-use data for simplified forest statistics, temporal consistency, and alignment with external and validation sources. First, Copernicus data were integrated with European Local Administrative Units (LAUs) to produce comprehensive information on forest cover and density at the local scale. Second, forest area estimates from HRL, CLC, and JAXA pixel counts were compared with FAO statistics at the country level. Results indicate that changes in methodologies and spatial resolution of the source data used in Copernicus HRL over the past decade affect the reported statistics. Copernicus HRL data show significant discrepancies compared to FAO data, while JAXA and CLC data are more aligned. These findings highlight the need to integrate better, present, and homogenize European forest information tools to ensure practical and accessible data.